Microdiscectomy for the Treatment of Lumbar Disc Herniation: An Evaluation of Reoperations and Long-Term Outcomes - Aichmair, Alexander; Du, Jerry Y.; Shue, Jennifer; Evangelisti, Gisberto; Sama, Andrew A.; Hughes, Alexander P.; Lebl, Darren R.; Burket, Jayme C.; Cammisa, Frank P.; Girardi, Federico P. (Evidence-Based Spine-Care Journal, 2014)
Design Retrospective case series.Objective The objective of this study was to assess the reoperation rate after microdiscectomy for the treatment of lumbar disc herniation (LDH) in patients with ≥ 5-year follow-up and identify demographic, perioperative, and outcome-related differences between patients with and without a reoperation.Methods The medical records, operative reports, and office notes of patients who had undergone microdiscectomy at a single institution between March 1994 and December 2007 were reviewed and long-term follow-up was assessed via a telephone questionnaire.Results Forty patients (M:24, F:16) with an average age at surgery of 39.9 ± 12.5 years (range: 18–80) underwent microdiscectomy at the levels L5–S1 (n = 28, 70%), L4-L5 (n = 9, 22.5%), L3–L4 (n = 2, 5.0%), and L1–L2 (n = 1, 2.5%). After an average of 40.4 ± 40.1 months (range: 1–128), 25% of patients (10/40) required further spine surgery related to the initial microdiscectomy. At an average postoperative follow-up of 11.1 ± 4.0 years (range: 5–19), additional symptoms apart from back and leg pain were reported more frequently by patients who underwent a reoperation (p = 0.005). Patient satisfaction was significantly higher in patients who did not undergo a reoperation (p = 0.041). For the Oswestry disability index, pain intensity (p = 0.036), and pain-related sleep disturbances (p = 0.006) were reported to be more severe in the reoperation group.Conclusions Microdiscectomy for the treatment of LDH results in a favorable long-term outcome in the majority of cases. The reoperation rate was higher in our series than reported in previous investigations with shorter follow-up. Although there were no statistically significant pre-/perioperative differences between patients with and without reoperation, our findings suggest a difference in self-reported long-term outcome measures.
Keywords: microdiscectomy; limited discectomy; long-term outcome; reoperation; Oswestry disability index; ODI; lumbar disc herniation